A proposal for needle projections in transcutaneous injection laryngoplasty using three-dimensionally reconstructed CT scans - Mohammad Nasir, Zuraini; Azman, Mawaddah; Mat Baki, Marina; Mohamed, Abdullah Sani; Thean, Yean Kew; Mohd Zaki, Faizah (Springer, 2021)
Purpose: This study aims to determine laryngeal dimension in relation to all three transcutaneous injection laryngoplasty (TIL) approaches (thyrohyoid, transthyroid and cricothyroid) using three-dimensionally reconstructed Computed Tomography (CT) scan and compare the measurements between sex, age group and ethnicity. Methods: CT scans of the neck of two hundred patients were analysed by two groups of raters. For thyrohyoid approach, mean distance from the superior border of the thyroid cartilage to the laryngeal cavity (THd) and mean angle from the superior border of the thyroid cartilage to mid-true cords (THa) were measured. For transthyroid approach, mean distance from mid-thyroid cartilage to mid-true cords (TTd) and Hounsfield unit (HU) at mid-thyroid cartilage (TTc) were measured. For cricothyroid approach, mean distance from the inferior border of the thyroid cartilage to the laryngeal cavity (CTd) and mean angle from the inferior border of the thyroid cartilage to mid-true cords (CTa) were measured. Results: There were statistically significant differences between males and females for all measurements except for CTa (p < 0.0001). No significant difference across age groups and ethnicities were found for all three approaches (p > 0.05). There was a significant fair positive correlation between age and TTc (p = 0.0002). For all measurements obtained, there were moderate to excellent inter-group consistency and intra-rater reliability. Conclusion: This study demonstrated a significant sex dimorphism that may influence the three TIL approaches except for needle angulation in the cricothyroid approach. The knowledge of laryngeal dimension is important to increase success in TIL procedure.